Hide and seek - Morgam , Michaela (UK, Oxford University Press, 1999)
Fitting the requirements of the National Literacy Strategy, National Curriculum in England and Wales, English Language 5-14 in Scotland, and Common Curriculum in Northern Ireland, this title guides pupils through the core skills associated with learning to read and write, with a diverse range of literary styles.